PENGARUH PENAMBAHAN BAKING SODA DALAM PAKAN TERHADAP KANDUNGAN SERUM GLUTAMAT PIRUVAT TRANSAMINASE DAN SERUM GLUTAMAT OKSALOASETAT TRANSAMINASE SAPI PERAH LAKTASI (Effect Of Sodium Bicarbonate in Addition Feed Content Serum Glutamic Pyruvic Transaminase And Serum Glutamic Oxaloacetic Transaminase Dairy Cows Lactation) - M. D. Prabowo; P. Sambodho; D. W. Harjanti; S. A.B. Santosa (Jurnal Ilmu dan Teknologi Peternakan, 2017)
The purpose of  this study  is  to assess  the dosage of baking soda  to  the feed on  the concentration of Serum Glutamate piruvat Transaminase (SGPT) and Serum Glutamate Oxalate Transaminase (SGOT). The material was used twelve Friesian Holstein lactation dairy cattle in the period I lactation month 5-6. The feed consists of elephant grass, concentrate and commercial pellet and sodium bicarbonate (NaHCO3). This research uses completely randomized design (RAL) with 3 treatments (T0, T1, T2) and 4 replications. The treatment given during the study was T0: without adding sodium bicarbonate to feed, T1: adding 0.8% sodium bicarbonate to feed, T2: adding 1.0% sodium bicarbonate to feed. Blood samples were taken 3 hours after feeding on the 21st day. SGPT and SGOT tests were performed using the Caretium NB-201 Semi-Auto Chemistry Analyzer tool. The result of SGPT value in T0, T1, and T2 treatment were 20.1 - 45.1 IU / l; 9.7 - 26.9 IU / l; And 9.7 - 24.4 IU / l. The SGOT values     of T0, T1, T2 respectively were 37.5 to 65.1 IU / l; 57.1 - 78.6 UI / l; And 40.5 - 67.4 UI / l. The addition of baking soda to the feed did not signifcantly infuence (P <0.05) on SGPT and SGOT concentrations in the blood of Dairy Cattle. The conclusion shows that the addition of Sodium bicarbonate into feed with concentration of 0.8% and 1.0% does not improve the performance of liver organ which is marked by no increase in SGPT and SGOT content in the blood.